BEHAVIOR HOLDING PERIOD DETERMINATION WITH MODERATING YIELD TO MATURITY IN INDONESIA AND MALAYSIA MANUFACTURING OPEN COMPANIES - Aliyah Nasution, Nur; Sadalia, Isfenti; Irawati, Nisrul (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Study this aim for test Influence Bid Ask Spread, Market value, and Variance Return, Dividend payout ratio to Holding Period with Yield to Maturity as moderating variable. Type of data used that is secondary data in the form of report finance companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange. Data analysis techniques used is Moderating Regression Analysis (MRA). Population in research this is whole company manufacturers listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange with population used _ totaling 488 companies with technique purposive sampling method. Variable independent study this is Bid Ask Spread, Market Value, Variance Return, and Dividend Payout Ratio. Variable dependent Mark company be measured with Holding Period. Whereas Yield to Maturity is variable moderation. Research results show Bid Ask Spread, Market Value, Return Variance, Dividend Payout Ratio by simultaneous take effect positive significant to Holding Period. Whereas by Partial Bid Ask Spread, Variance Return and Dividend Payout Ratio take effect positive and significant to Holding Period. Market Value take effect positive However no significant to Holding Period. Then addition Yield to Maturity as moderating variable between variable independent to variable dependent results obtained _ is Bid Ask Spread is positive and significant to Holding Period through Yield to Maturity. Variance Return take effect positive no significant to Holding Period through Yield to Maturity. Whereas Market Value and Dividend Payout Ratio take effect negative no significant to Holding Period through Yield to Maturity.